2021
DOI: 10.1088/1674-1056/abcf98
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting anisotropy and vortex pinning in CaKFe4As4 and KCa2Fe4As4F2 *

Abstract: The vortex pinning determining the current carrying capacity of a superconductor is an important property to the applications of superconducting materials. For layered superconductors, the vortex pinning can be enhanced by a strong interlayer interaction in accompany with a suppression of superconducting anisotropy, which remains to be investigated in iron based superconductors (FeSCs) with the layered structure. Here, based on the transport and magnetic torque measurements, we experimentally investigate the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(93 reference statements)
1
4
0
Order By: Relevance
“…It is found that the U of 3.5 UC single crystal is slightly smaller than that of 2.5 UC single crystal, which suggests that the flux pinning in 2.5 UC single crystal is stronger than that in 3.5 UC single crystal. U decreases with the increase of fields, which is similar to iron-based superconductors [39,40] and other cuprates [41,42]. In addition, the thermal activation energy U is almost proportional to lnH at all measurement ranges, indicating a 2D structure of the vortices [39,42].…”
Section: Resultssupporting
confidence: 53%
“…It is found that the U of 3.5 UC single crystal is slightly smaller than that of 2.5 UC single crystal, which suggests that the flux pinning in 2.5 UC single crystal is stronger than that in 3.5 UC single crystal. U decreases with the increase of fields, which is similar to iron-based superconductors [39,40] and other cuprates [41,42]. In addition, the thermal activation energy U is almost proportional to lnH at all measurement ranges, indicating a 2D structure of the vortices [39,42].…”
Section: Resultssupporting
confidence: 53%
“…Typically the defects induced by impurities or ion irradiations should have a size of several to tens of nanometers to supply the effective pinning centers [13,44]. Another factor worthy of attention is that the activation energy shows an anti-correlation with the anisotropy in the FeSCs [27]. Thus, the enhancement of Γ from 8.0 to 9.2 induced by Co-doping may be the dominant and intrinsic reason for the reduction of U 0 in Co-doped samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have observed a significant suppression of the activation energy for the flux flow in the ultra-thin sample of KCa 2 Fe 4 As 4 F 2 [12]. The correlation between the activation energy and the SC anisotropy in FeSCs was also uncovered [27].…”
Section: Introductionmentioning
confidence: 93%
“…Pinning plays a crucial role in determining the vortex dynamics in the mixed state of type-II superconductors, which is important for lossless transport in the applications of superconductors. [1][2][3][4][5][6][7][8][9] It has been suggested to introduce many defects as effective pinning centers against the driving force of magnetic flux flow. Of them, twin boundaries may be the most significant anisotropic pinning defects in the cuprate compound YBa 2 Cu 3 O 7−x (YBCO).…”
Section: Introductionmentioning
confidence: 99%